2020
DOI: 10.1002/jcp.29726
|View full text |Cite
|
Sign up to set email alerts
|

Roles of noncoding RNAs in drug resistance in multiple myeloma

Abstract: Despite the administration of new effective drugs in recent years, relapse and drug resistance are still the main obstacles in multiple myeloma (MM) treatment, making MM an incurable disease. To overcome drug resistance in MM, it is critical to understand the underlying mechanisms of malfunctioning gene expression and develop novel targeted therapies. During the past few decades, with the discovery and characterization of noncoding RNAs (ncRNAs), the landscape of dysregulated ncRNAs of cancers as well as their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 123 publications
(185 reference statements)
0
2
0
Order By: Relevance
“…With the continuous progress of diagnosis and treatment technologies, the overall survival and quality of life of MM patients have been greatly improved, but it remains an incurable malignant tumor (18). In recent years, lncRNAs have been found to play extremely important roles in the course of various neoplastic diseases, including MM (19,20). This study first found that lncRNA AL was highly expressed in MM samples and cell lines and was significantly correlated with the ISS stage of patients.…”
Section: Discussionmentioning
confidence: 71%
“…With the continuous progress of diagnosis and treatment technologies, the overall survival and quality of life of MM patients have been greatly improved, but it remains an incurable malignant tumor (18). In recent years, lncRNAs have been found to play extremely important roles in the course of various neoplastic diseases, including MM (19,20). This study first found that lncRNA AL was highly expressed in MM samples and cell lines and was significantly correlated with the ISS stage of patients.…”
Section: Discussionmentioning
confidence: 71%
“…ncRNAs are those regions of the genome which are not transcribed into proteins but are involved, nonetheless in regulating transcriptional status of genes in the genome by transcriptional repression [154] . The role of ncRNAs, such as lncRNAs, microRNA (miRNAs), ceRNAs, circRNA, in MM biology has been recognized in the literature [155] . Fig.…”
Section: Molecular Aspects Of MMmentioning
confidence: 99%